2004
DOI: 10.1159/000077419
|View full text |Cite
|
Sign up to set email alerts
|

The Position of Pranlukast, a Cysteinyl Leukotriene Receptor Antagonist, in the Long-Term Treatment of Asthma

Abstract: Background: Adverse effects, tachyphylaxis, and the position of pranlukast, a cysteinyl leukotriene receptor antagonist, in asthma treatment have not been fully established. Objectives and Methods: To address these questions, adverse effects and long-term efficacy of pranlukast were evaluated in 82 patients [28 patients with moderate asthma (group I), 27 with severe persistent asthma not on oral corticosteroid (OCS; group II) and 27 with severe persistent asthma on OCS (group III)] at 4 and 16 weeks. In the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Recent studies have also supported the use of long-acting β 2 agonists and ICS together [6, 7, 8, 9, 10, 11]. An alternative approach is to add a leukotriene receptor antagonist to an ICS [12, 13]. Montelukast is a leukotriene receptor antagonist that improves asthmatic inflammation and prevents bronchoconstriction [14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also supported the use of long-acting β 2 agonists and ICS together [6, 7, 8, 9, 10, 11]. An alternative approach is to add a leukotriene receptor antagonist to an ICS [12, 13]. Montelukast is a leukotriene receptor antagonist that improves asthmatic inflammation and prevents bronchoconstriction [14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…A long-term follow-up study has confirmed the safety of LTRAs as well as the absence of the tachyphylaxis induced by β2-agonists [94].…”
Section: Safetymentioning
confidence: 71%
“…Although no severe adverse effects were described in their study, long-term use of cimetidine has, in general, adverse side effects, such as inhibition of P450 system, headache, and gynecomastia. In contrast pranlukast has long been used for treating asthma chronically with little adverse effects 20 …”
Section: Discussionmentioning
confidence: 99%